Comparison of surgical treatments of tumor-induced osteomalacia in different locations in the lower limbs: A retrospective study. Issue 11 (March 2019) - Li, Ye; Li, Yatong; Hui, Min; Liu, Yong; Liu, Xiaoding; Jin, Jin; Gao, Peng
Abstract : Abstract: Tumor-induced osteomalacia (TIO) is a rare disease that behaves benignly. Very few reports about the features of the responsible tumors according to anatomical locations have been presented. In this retrospective study of 53 patients with TIO-associated tumors in the foot/ankle, tibia and femur, we compared preoperative, postoperative, and follow-up courses, including alkaline phosphatase, phosphorus, and fibroblast growth factor 23, to compare the characteristics of TIO-associated tumors in these 3 locations (level of evidence: therapeutic level III). Patients in the foot/ankle group had longer disease courses and therefore a significantly higher complication rate ( P  < .001). All TIO-associated tumors in the foot/ankle group involved soft tissue ( P  = .021), whereas most lesions in the tibia group involved bone, and therefore had much higher concentrations of alkaline phosphatase ( P  = .020). Additionally, serum phosphorus took much longer to normalize after surgery in the foot/ankle group than that in the other 2 groups ( P  = .004). Consequently, symptom remission was much better in the tibia and femur groups ( P  = .008). Moreover, the Ki 67 index in TIO-associated tumors was significantly higher in the foot/ankle group ( P  < .001) and the recurrence rate in this group was markedly higher ( P  = .002). The TIO-associated tumors in the foot/ankle are characteristically of occult onset, more soft-tissue involvement, and more readily recurrence. More knowledge and examinations are necessary to enable early diagnosis, radical treatments, and minimize recurrence. New therapies are welcomed and needed.